Tantangan dan Peluang: Paradigma Pemidanaan Mengenai Restorative Justice Sebagai Rechterlijke Pardon Dalam KUHP Nasional - Andi Annisyah Tenri Sanna (Fakultas Hukum, Universitas Warmadewa, 2025)
This article discusses a paradigm shift in sentencing in the application of Restorative Justice and Judicial Pardon (Rechterlijk Pardon). The aim of this discussion is to determine the qualification of differences in a sentencing concept using the RJ (Restorative Justice) approach and Rechterlijke Pardon, and whether they can be applied simultaneously or separately. The method used in this study is doctrinal research, focusing on the study of rules, principles, and norms related to the resolution of criminal cases. The results of this study indicate that Restorative Justice and Judicial Pardon have distinct aspects; however, in essence, Rechterlijke Pardon originates from a restorative justice approach. It can be stated that both Rechterlijke pardon and restorative justice operate in parallel. The 2023 Criminal Code (KUHP) also shows that Rechterlijke pardon and restorative justice should be aligned with the Criminal Procedure Code (KUHAP).